If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3+y=-4
We move all terms to the left:
1/3+y-(-4)=0
We add all the numbers together, and all the variables
y+4+1/3=0
We multiply all the terms by the denominator
y*3+1+4*3=0
We add all the numbers together, and all the variables
y*3+13=0
Wy multiply elements
3y+13=0
We move all terms containing y to the left, all other terms to the right
3y=-13
y=-13/3
y=-4+1/3
| M/3+m6=8 | | 4(-7x+2)=64 | | 5x2−4x−7=1−x | | 15-1/2x2=x | | 4x=18-(-4) | | `-12=7-h | | 34=–(m+3) | | 11b+2=90 | | 3/4=x/2+2/3 | | -12x-9+24+4=23 | | 3c-10=5c-40 | | 57=3(x-2) | | 269.50-x=14 | | 7x/5-5=9 | | $269.50-x=14 | | 10x+5=4x+1 | | -6y+5=53 | | x²-x-6=0 | | $269.50-a=14 | | 10x²-13x-3=0 | | 5+b7=-2 | | w+26=2w | | -6+-1x+x²=0 | | 0.25x-1=0.125(7x-2) | | c+16=9c | | a^2-3=46 | | 8b-6(10-3b)=7 | | 10t^2-2t+3=0 | | -6+-1x+x2=0 | | –6(2+a)=–48 | | -18n+12=-16n-16 | | 5x^-2x-115=0 |